2013
DOI: 10.1002/prot.24263
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of structural transitions during GNNQQNY aggregation

Abstract: Amyloid protein aggregation characterizes many neurodegenerative disorders, including Alzheimer's, Parkinson's, and Creutzfeldt-Jakob disease. Evidence suggests that amyloid aggregates may share similar aggregation pathways, implying simulation of full-length amyloid proteins is not necessary for understanding amyloid formation. In this study, we simulate GNNQQNY, the N-terminal prion-determining domain of the yeast protein Sup35 to investigate the thermodynamics of structural transitions during aggregation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 75 publications
(213 reference statements)
2
23
0
Order By: Relevance
“…The model is transferable in that it aims at describing the essential features of a variety of amino-acid sequences, rather than an accurate reproduction of any specific one. After parametrization, it was demonstrated that the PLUM model folds several helical peptides [6,[22][23][24][25], stabilizes β-sheet structures [6,[26][27][28][29], and is useful for probing the conformational variability of intrinsically disordered proteins [30]. We also considered four minor reparametrizations of the PLUM model: 1. the side chain van der Waals radius is decreased to 90% of its original value [20].…”
Section: Plummentioning
confidence: 99%
“…The model is transferable in that it aims at describing the essential features of a variety of amino-acid sequences, rather than an accurate reproduction of any specific one. After parametrization, it was demonstrated that the PLUM model folds several helical peptides [6,[22][23][24][25], stabilizes β-sheet structures [6,[26][27][28][29], and is useful for probing the conformational variability of intrinsically disordered proteins [30]. We also considered four minor reparametrizations of the PLUM model: 1. the side chain van der Waals radius is decreased to 90% of its original value [20].…”
Section: Plummentioning
confidence: 99%
“…19 The model is transferable in that it aims at describing the essential features of a variety of amino-acid sequences, rather than an accurate reproduction of any specific one. After parametrization, it was demonstrated that the PLUM model folds several helical peptides, 19,[29][30][31][32] stabilizes β-sheet structures, 19,26,[33][34][35] and is useful for probing the conformational variability of intrinsically disordered proteins. 36…”
Section: Plummentioning
confidence: 99%
“…Without changing the force-field parameters, the model can also stabilize different helical peptides and assemble β-sheet-rich oligomers. 31 The CG model has been applied to a variety of scenarios involving helical peptides, 34,35 aggregation of β-rich peptides, 36 and β-barrel formation at the interface between virus capsid proteins. 37 The lipid model maps a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) lipid into 16 beads, using 8 bead types to distinguish different chemical moieties.…”
Section: A Coarse-grained Simulations: Plum Force Fieldmentioning
confidence: 99%